MENUMBUHKAN SIKAP SALING MENGHARGAI ANTAR PESERTA DIDIDK DENGAN PEMBIASAAN SENYUM SAPA UNTUK MENCEGAH KEKERASAN ANTAR SISWA SEKOLAH DASAR - Lestari, Noviana; Siregar, Veni Veronica (Universitas Negeri Medan, 2023)
The issue of bullying is not over in the education sector. The rising number of students who are bullied demonstrates that students are not receiving sufficient character development and education. With this exploration, applying common regard for grins and good tidings means to forestall harassing of understudies. Specialists utilized expressive subjective examination strategies with information assortment methods of perception, interviews, documentation. The outcomes got from this study are that understudies have a feeling of shared regard and understudies have fearlessness.